Evaluation General Diploma Program in Education at the Islamic University of Madinah - Saudi Arabia - in Light of the Overall Quality of the Perspective of Students Standards - Ghali Dohyran ALlogmani (University of Science and Technology, Yemen, 2015)
This study aims to investigate the availability of comprehensive quality standards in the Program of General Diploma in Education, at the Islamic University, Saudi Arabia from the viewpoint of the students. The researcher used the descriptive method to collect data. The tool used was a questionnaire composed of 45 statements, which are distributed into five areas: objectives, teaching methods and teaching aids, the content of the curriculum, assessment, and practical education. The number of the students who responded to the questionnaire was (233). The study came up with the following results: - The study found that students see the availability of comprehensive quality standards were Moderate as all.       - There was no statistically significantly different in comprehensive quality standards related to type of students work. - There were statistically significant differences in comprehensive quality standards related to major, the time between drop out of university and registration in the program of General Diploma in Education.